Magnetic field induced lattice effects in a quasi-two-dimensional organic conductor close to the Mott metal-insulator transition - de Souza, Mariano [UNESP]; Bruehl, Andreas; Strack, Christian; Schweitzer, Dieter; Lang, Michael (Amer Physical Soc, 2012)
We present ultra-high-resolution dilatometric studies in magnetic fields on a quasi-two-dimensional organic conductor kappa-(D8-BEDT-TTF)(2)Cu[N(CN)(2)]Br, which is located close to the Mott metal-insulator (MI) transition. The obtained thermal expansion coefficient, alpha(T), reveals two remarkable features: (i) the Mott MI transition temperature T-MI = (13.6 +/- 0.6) K is insensitive to fields up to 10 T, the highest applied field; (ii) for fields along the interlayer b axis, a magnetic field induced (FI) phase transition at T-FI = (9.5 +/- 0.5) K is observed above a threshold field H-c similar to 1 T, indicative of a spin reorientation with strong magnetoelastic coupling.